Efisiensi Pemanfaatan Berbagai Faktor Produksi pada Peternakan Itik Rakyat (Survey di Kabupaten Indramayu) - Herlina, Linda; Fitriani, Anita (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The duck farming industry exhibits potential for expansion, offering possibilities for increased income from its operations. In November 2021, a study was conducted in Indramayu Regency to assess the technical, allocative, and economic efficiency levels in utilizing production factors within duck farming enterprises. Employing a survey method, 100 breeders served as observation units, and variables such as the quantity of products (Y), seeds (X1), feed (X2), cages (X3), and labor (X4) were examined. The analysis employed the Cobb-Douglas function model. Results revealed inefficiencies in the utilization of production factors in the region. Technical efficiency in the livestock sector registered a value of 1.282 (seeds = 0.642; feed = 0.310; cages = 0.162; labor = 0.168). Price efficiency stood at 6.891 (seeds = 4.149; feed = 1.523; cages = 0.876; labor = 0.343), while economic efficiency reached 3.351 (seeds = 2.664; feed = 0.487; cage = 0.142; labor = 0.058). The duck farming endeavors in the studied area have not yet attained optimal efficiency levels, indicating a situation of increasing returns to scale.